The journey of Indonesian nurse migration: a scoping review - Rifky Octavia Pradipta; Ferry Efendi; Abdullah Saleh Alruwaili; Mohammad Rizal Diansya; Anna Kurniati (PAGEPress Publications, 2023)
The migration of nurses from Indonesia to other foreign countries is an inevitable part of the global mobility of the nurse profession. This phenomenon requires investigation to understand the current trajectories of Indonesian nurses in the global market. This scoping review aimed to investigate the Indonesian nurses' mobility to the international healthcare market. A scoping review of primary research addressing Indonesian nurses migration journey overseas. A range of databases were searched, including Scopus, Web of Science Clarivate Analytics, Cumulative Index to Nursing and Allied Health Literature (CINAHL), and PubMed. A systematic process was performed guided by the work of Arksey and O'Malley. Four databases were searched, and 68 articles were retrieved. After screening articles and abstracts, 19 full texts were assessed for eligibility, and finally, 17 studies were further analyzed and synthesized. Eleven qualitative studies, five quantitative study and one literature review study met inclusion criteria, emphasizing the three phases of migration: pre-migration, migration and post-migration. The destination countries of Indonesian nurses including Japan, Kuwait, Saudi Arabia and Taiwan. At the pre-migration stage there are several aspects that must be considered, there were: language, understanding of the job position, reason to work and comprehensive understanding of the destination countries. Migration stage include issues language, deskilling, mental health, unclear career path, cultural adaptation, lack of religious services and homesickness. At the post-migration stage includes deskilling, brain waste and re-integration with brain circulation platform. The comprehensive approach of Indonesian nurses migration from pre-migration, migration and post-migration has shown us the trajectory of Indonesian nurses in international migration. Understanding the bottle neck of each stage with improve policy support is needed to create safe and sound migration channel for Indonesian nurses. This review highlighted to the need for future research in key areas such as the impact of nurse migration on Indonesia's health systems.